Mapping Environmental Quality Indices of Dhaka City by Using Geospatial Techniques - Ahmed, Asib; Onny, Orna Rahman (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Dhaka, the city of over 10 million people is one of the most polluted cities due to rapid urbanization, commercial development and population pressure. The present study assessed an overall environmental quality of Dhaka South City Corporation (DSCC) and Dhaka North City Corporation (DNCC) using an Environmental Quality Index (EQI) based on five indices: Air Quality Index (AQI), Water Quality Index (WQI), Soil Quality Index (SQI), Noise Quality Index (NQI), and Vegetation Index (VI). The final EQI was determined through selecting components from background literature and an overlay analysis using predefined weights for each distinct indices. The study reveals that the west and west-central part of DSCC have experienced the most severe environmental degradation, affecting noise levels, vegetation cover, air, soil, and water quality. However, the air is less polluted especially in the peripheral zones of the city corporations. Overall, the study indicates that the environmental quality of DNCC is comparatively better than DSCC. The results of the study provides an insight on environmental quality of the city for legislators, urban planners, environmentalists, and researchers to monitor and preserve environmental quality in making the city livable, healthy and sustainable. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(2), 2023, P 41-53